2013
DOI: 10.1186/1749-8090-8-43
|View full text |Cite
|
Sign up to set email alerts
|

The role of remote ischemic preconditioning on postoperative kidney injury in patients undergoing cardiac and vascular interventions: a meta-analysis

Abstract: The objective of this study was to perform a meta-analysis of randomized controlled trials (RCTs) investigating whether a remote ischemic preconditioning (RIPC) protocol provides renal protection to patients undergoing cardiac and vascular interventions. Searches were conducted in the databases PUBMED, EMBASE and Cochrane Library. RCTs that fulfilled the inclusion criteria and addressed the clinical questions of this analysis were further assessed. We identified ten studies with a total of 924 patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
(84 reference statements)
2
32
0
Order By: Relevance
“…Notable in this regard is so called “remote preconditioning”, whereby recurrent bouts of upper and/or lower limb ischemia are induced by recurrently inflating and deflating blood pressure cuffs (2426). The goal to release unknown tissue ‘conditioning factors’ into the systemic circulation that will trigger protective tissue responses (e.g., in brain, heart, liver, and kidney).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable in this regard is so called “remote preconditioning”, whereby recurrent bouts of upper and/or lower limb ischemia are induced by recurrently inflating and deflating blood pressure cuffs (2426). The goal to release unknown tissue ‘conditioning factors’ into the systemic circulation that will trigger protective tissue responses (e.g., in brain, heart, liver, and kidney).…”
Section: Introductionmentioning
confidence: 99%
“…The goal to release unknown tissue ‘conditioning factors’ into the systemic circulation that will trigger protective tissue responses (e.g., in brain, heart, liver, and kidney). Despite its appeal, this approach has had only questionable success (2426), likely due to the following: 1) the ‘factors’ released from post ischemic limbs that might induce ‘preconditioning’, and how much ‘factor’ release is required to induce this state, are unknown; 2) the cellular pathways by which such ‘factors’ impact distant organs to induce cytoresistance have not been defined; and 3) it is impossible to judge whether the desired ‘pre-conditioning’ actually develops in any given individual.…”
Section: Introductionmentioning
confidence: 99%
“…A more practical approach may be achieved using remote IPC (RIPC). RIPC has been shown to provide renal protection to patients undergoing cardiac and vascular interventions . Recently a group of Chinese urologists reported that slight lower limb ischemia significantly reduced renal impairment within 1 month after laparoscopic partial nephrectomy .…”
Section: Introductionmentioning
confidence: 99%
“…Li L in a review study indicated that the main reason for the contradicting results in RIPC studies is different definition for AKIA (23). Brevoord also reviewed the literatures for renal protective role of RIPC after heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…He also concluded no difference between RIPC and control group. He indicated that as serum creatinine is the mostly used biomarker for detecting AKI (23-25), which might not change significantly in an acute setting. we have also observed its significant decrease after 24 hours.…”
Section: Discussionmentioning
confidence: 99%